Estratégias de fundação colonial de uma vespa social primitiva (Vespidae: Polistinae: Polistes canadensis) em um crescente de aridez - Andrade Filho, Fernando César Moura de (2015)
In some primitively social insects, the absence of distinct morphological castes leads to reproductive plasticity during nest founding. However, environmental constraints select for viable reproductive options. These constraints are well known in temperate locations and distinct from tropical semi-arid environments. We tested the hypothesis that aridity-related constraints on independent nesting decreases the fitness pay-offs to solitary foundresses in a primitively social wasp (Polistes canadensis). 95 colonies were monitored during a six month period in three distinctively arid regions. Colony fail, colony survival and colony reproductive success from each of two (solitary and cooperative) nesting patterns were quantified. Local foundresses population size was larger in less arid locations (Parque do Cocó: n = 142, Pentecoste: n = 86, Serra das Almas: n = 46). In more arid regions, all reproductive successful colonies were founded in the most rainy month of the rainy season (region [GLM: LR = 18.5, d.f. = 2, p < 0.0001***], foundation period [GLM: LR = 5.7, d.f. = 1, p = 0.01*]). Among the foundation period surviving colonies, solitary nesting reproductive success (measured as pupal production) decreased with aridity (nesting strategy [GLM: LR = -6.2, d.f. = 1, p = 0.01*], region [GLM: LR = -18.4, d.f. = 2, p = 0.0001***]). We conclude that aridity constraints reproduction in a primitively social wasp and, in more arid environments, favors the foundations occurred during momentary pulses of high rainfall.